Pemanfaatan Perpustakaan Sekolah Sebagai Sumber Belajar Siswa SD Inpres 12/79 Biru II Kecamatan Tanete Riattang Kabupaten Bone - rosmalah rosmalah; Ayu RIska (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2019)
The problem examined in this study is the lack of maximum utilization of school libraries as a source of learning. The focus of the Problem: how is the use of the school library as a learning resource for students of SD Inpres 12/79 Biru II Tanete Riattang District, Bone Regency. The purpose of this study is to describe the use of the school library as a source of learning for students of SD Inpres 12/79 Biru II, Tanete Riattang Subdistrict, Bone Regency. The approach used in this study is qualitative. This type of research is descriptive research. This research was conducted from class I-VI SD Inpres 12/79 Biru II in February-April 2018. Subjects in this study were students of class I-VI SD Inpres 12/79 Biru II, Tanete Riattang Subdistrict, Bone Regency, which numbered 30 people consists of 16 men and 14 women, homerooms, librarians, and principals. Data collection in this study using observation sheets, interviews, and documentation. The data analysis technique uses data reduction, data presentation, and draw conclusions. The results of this study can be seen that the use of school libraries as learning resources is not optimal. So, it can be concluded that the use of the school library as a source of learning for students of SD Inpres 12/79 Biru II, Tanete Riattang Subdistrict, Bone Regency has not run optimally.